Program Radio 105 RAU FM Padang Sidimpuan Dalam Mempertahankan Pendengar - Hasibuan, Darussalam; Daulay, Maraimbang; Deni, Indira Fatra (Journal of Computer Science and Information System(JCoInS), 2024)
This study entitled Radio 105 RAU FM Padang Sidimpuan program in maintaining listeners. The purpose of this study was to determine the radio Program 105 RAU FM Padang Sidimpuan in maintaining listeners. This study uses qualitative descriptive method by using data collection techniques such as observation, interview, and documentation, where the subject of research is the radio program 105 RAU FM Padang Sidimpuan.  The focus of researchers in this study is the RAU radio program in maintaining listeners can be seen from the presentation of information needed by listeners, understanding of broadcast topics, the most popular programs listeners, factors causing the decline in listeners and solutions, and broadcast programs that are interesting for listeners. The results of this study is the Radio program 105 RAU FM Padang Sidimpuan in maintaining listeners run effectively on the presentation of information needed listeners, understanding the topic of the broadcast, the most popular programs listeners, factors causing the decline in listeners and solutions, and broadcast programs that are interesting for listeners.